11th international congress molded interconnect devices : scientific proceedings : selected, peer reviewed papers from the 11th International Congress Molded Interconnect Devices (MID 2014), September 24-25, 2014, Nuremberg / Fuerth, Germany - Franke, Jörg (Prof. Dr.-Ing.) (Advanced materials research ;, 2014)
Collection of selected, peer reviewed papers from the 11th International Congress Molded Interconnect Devices (MID 2014), September 24-25, 2014, Nuremberg / Fuerth, Germany. The 16 papers are grouped as follows: Chapter 1: Development and Prototyping, Chapter 2: Printing Technologies, Chapter 3: Materials and Manufacturing, Chapter 4: Manufacturing Processes, Chapter 5: Assembly Technologies and Inspection, Chapter 6: Quality and Reliability. Keyword: Printing Technologies, Materiala Manufacturing, Manufatruting processes, Inspection, assemply technologies, quality testing The 16 papers collected here are from the 11th International Congress Molded Interconnect Devices (MID 2014), held in September 2014 in Nuremberg/Fuerth, Germany. Technology specialists from Europe, the US, and Taiwan address development and prototyping, printing technologies, materials and manufacturing, manufacturing processes, assembly technologies and inspection, and quality and reliability. -- Electronic components and devices-- Electronic engineering-- Materials science.